The applications of polysaccharides in dentistry - Yang, Zhijing; Liu, Weiwei; Liu, Huimin; Li, Rong; Chang, Lu; Kan, Shaoning; Hao, Ming; Wang, Dongxu (Frontiers in Bioengineering and Biotechnology, 2022)
Polysaccharides are natural polymers widely present in animals, plants, and several microorganisms. Polysaccharides have remarkable properties, including easy extractions, degradability, and renewability, and have no apparent toxicity, making them ideal for biomedical applications. Moreover, polysaccharides are suitable for repairing oral tissue defects and treating oral diseases due to their excellent biocompatibility, biosafety, anti-inflammatory, and antibacterial properties. The oral cavity is a relatively complex environment vulnerable to numerous conditions, including soft tissue diseases, hard tissue disorders, and as well as soft and hard tissue diseases, all of which are complex to treat. In this article, we reviewed different structures of natural polysaccharides with high commercial values and their applications in treating various oral disease, such as drug delivery, tissue regeneration, material modification, and tissue repair.